2009
DOI: 10.1175/2008waf2222140.1
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Multimodel Ensemble Approach to Seasonal Prediction

Abstract: A probabilistic multimodel ensemble prediction system (PMME) has been developed to provide operational seasonal forecasts at the Asia–Pacific Economic Cooperation (APEC) Climate Center (APCC). This system is based on an uncalibrated multimodel ensemble, with model weights inversely proportional to the errors in forecast probability associated with the model sampling errors, and a parametric Gaussian fitting method for the estimate of tercile-based categorical probabilities. It is shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…The choice of the Gaussian distribution for the seasonal precipitation totals is based on [15] where it was shown that the use of gamma-, empirical, and the Gaussian distributions provides comparable results.…”
Section: Methods Of Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the Gaussian distribution for the seasonal precipitation totals is based on [15] where it was shown that the use of gamma-, empirical, and the Gaussian distributions provides comparable results.…”
Section: Methods Of Estimationmentioning
confidence: 99%
“…To minimize the influence of random errors, the individual model forecasts were given weights inversely proportional to the maximum random error in forecast probability due to the error in the estimate of the mean m predicted by each model. This combination method was developed in APCC and described in [15]. According to the square root rule, the error of the mean e m (sampling error) is inversely proportional to the square root of the sample size (ensemble size) n:…”
Section: Methods Of Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal climate forecasts are usually issued in tercile probabilities, which are probability of below-normal (BN), near-normal (NN), and above-normal (AN) [10]. Climate forecasting can facilitate risk assessment, preparation and adaptation for global decision-making and planning in various sectors such as energy, water and food security [11].…”
Section: Fundamental Principle Of Stochastic Weather Generatorsmentioning
confidence: 99%
“…Multimodel ensemble (MME) techniques have been used to produce skillful seasonal forecasts by reducing uncertainties in the individual global climate model (e.g., Krishnamurti et al, 1999;Palmer and Shukla, 2000). The Asia-Pacific Economic Cooperation Climate Center (APCC) has produced 6-month lead predictions based on a fully operational MME seasonal forecast system since 2005 (Min et al, 2009).…”
Section: Introductionmentioning
confidence: 99%